Design and Implementation of a Tracer Study Application Website with the Laravel Framework - Prasetyo, Junaedi Adi; Ayatullah, M Dimyati Dimyati; Zakaria, Muhammad Nanak; Rohman, Abdur (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2026)
Tracer studies serve as a vital mechanism for monitoring alumni career development and obtaining feedback that informs the continuous improvement of educational management and graduate quality. Recognizing the strategic importance of alumni outcomes as indicators of institutional performance, we developed a web-based tracer study information system in SMK Ihya Ulumuddin. The system was designed using the Unified Modelling Language (UML) approach and implemented with the Hypertext Pre-processor (PHP) programming language, the XAMPP database, and the Laravel framework. Evaluation was conducted through beta testing employing the black-box method to ensure system reliability and functionality. The resulting application provides accurate and comprehensive alumni data, prevents duplication, strengthens database security, and enables efficient online questionnaire distribution. Furthermore, the system accelerates alumni data collection and facilitates a more systematic evaluation of tracer study outcomes. This innovation contributes to enhancing institutional capacity in managing alumni information and supports the production of competitive and career-ready graduates